The Role of Healthcare Worker Motivation in the Relationship between Work Culture, Patient Satisfaction, and Performance at a Primary Healthcare Clinic - Anita Ekasari; Dwi Orbaningsih; Tri Cicik Wijayanti; Nisa Arifani (International Journal of Public Health Excellence (IJPHE), 2026)
Healthcare worker performance plays a crucial role in determining the quality of services in primary healthcare clinics. Organizational and service-related factors, such as work culture, patient satisfaction, and healthcare worker motivation, are considered important determinants of performance. However, empirical evidence regarding the mediating role of healthcare worker motivation in primary healthcare settings remains limited. This study aimed to examine the relationship between work culture and patient satisfaction with healthcare worker performance, both directly and indirectly through healthcare worker motivation as a mediating variable, in a primary healthcare clinic. An observational analytic study with a quantitative approach was conducted at a primary inpatient healthcare clinic in Mojokerto Regency, Indonesia, during September–October 2025. The study involved 20 healthcare workers and 50 patients, selected using total sampling. Data were collected through structured questionnaires and analyzed using descriptive statistics and Spearman correlation tests to assess relationships among variables. The results showed that work culture was positively associated with employee motivation (r = 0.476; p = 0.034), while patient satisfaction was positively related to healthcare worker performance (r = 0.446; p = 0.049). Healthcare worker motivation also demonstrated a significant mediating role in the relationship between work culture and healthcare worker performance (r = 0.508; p = 0.022). Improving healthcare worker performance in primary healthcare clinics requires an integrated managerial approach that emphasizes strengthening work culture, enhancing patient satisfaction, and maintaining healthcare worker motivation to support sustainable improvements in service quality.